Abstract Review DIGITAL LEARNING USING TABLETS IN A PRISON EDUCATION CENTRE (African Journal of Public Administration & Management, 2026)
INITIAL REFLECTIONS ON TEACHING AND LEARNING USING TABLETS IN A PRISON EDUCATION CENTRE. Joseph Kariuki Mugatha,Assistant Superintendent of Prisons,Naivasha Maximum Security Prison,mugathakariuki@gmail.com ABSTRACTThe reflections reported in this paper involve an intervention using a tablet as a tool for enhancing teaching and learning in a Maximum Security Prison Education Centre in Kenya. The tablet is connected wirelessly to a server running the tutor-web education software, installed at the Centre. The prison staff-teachers first duty is security, containment and then teaching - rehabilitation. With these priorities, the prison-teachers sometimes do not attend to their class lessons for hours or days and hence inmate-students miss continued seamless class instructions. To address this challenge, the use of tablet was implemented as a tool to facilitate continued instructions times and subsequent learning. The participants were high school students in the secondary section of the Centre. Findings show that the use of technology did not only facilitate continued learning, but also changed the inmate-students’ negative attitude towards learning, motivated them and improved their overall performance. Challenges of using the tablet as a tool were noted. In general, the project continues to facilitate achievement of the mission of Kenya Prison Service (KPS) of containment and rehabilitation of offenders, responsive administration of justice, social reintegration and community protection. Future improvements on the project have been suggested. The findings inform the government’s implementation of digital learning of students which is key for the development of the country. Keywords: Prison; tablet, teaching and learning, technology. INTRODUCTION. (not required in the abstract)